Improving Performance of Silicon Thermo-Optic Switch by Combing Spiral Phase Shifter and Optimized Pulse Driving - Dongdong Lin; Wei Cheng; Shangqing Shi; Pengcheng Liu; Mengjia Lu; Tong Lin; Guohua Hu; Binfeng Yun; Yiping Cui (IEEE Photonics Journal, 2022)
For the silicon photonics integrated circuits, the optical switch plays a vital role in many applications. Large scale integration requires low switching power and fast switching speed. However the switching time and switching power of silicon thermo-optic switch are typically limited to tens of micro-seconds and tens of milli-watts, respectively. In this paper, we designed and fabricated a silicon thermo-optic switch with spiral optical phase shifters, which can reduce the switching power from 21.5 mW to 8.73 mW compared to the optical switch with straight phase shifters. Furthermore, we optimized the pulse driving, we proposed the calculation formula of the pulse voltage, and the overall quantitative scheme of the pulse voltage and pulse width. By adopting the optimized pulse driving, the switching time is reduced from 27 μs to 4 μs. The proposed silicon thermo-optic switch unit with optimized pulse driving is very promising for the applications where large scale integration of optical switches is needed.